Electrolyte Membrane of Poly(ethylene oxide)-Lithium-5(6)-Nitrobenzimidazole for Lithium Batteries Application - Ryplida, Benny
Lithium ion batteries are one of the alternative energy sources that are currently developed as electrode, electrolyte, or separator. In the electrolyte sector, the most promising development is the presence of the polymer electrolytes. However, the current development is constrained in the use of polymer electrolyte because the electrolyte salt used will produce toxic or explosive compounds when decomposed. Based on these facts, the author performed the synthesis of a compound which was considered friendly to the environment such as imidazoles derivatives. The synthesized compound is benzimidazole derivatives, namely 5(6)-nitrobenzimidazole. The compound was synthesized by the nitration reaction on benzimidazole. The product showed the existence of a peak at 1354 cm-1 which was the vibration of nitro group (-N=O). The synthesized 5(6)-nitrobenzimidazole then treated with the aqueous solution of lithium carbonate to form lithium-5(6)-nitrobenzimidazole salt using deprotonation reaction of hydrogen on the nitrogen in the imidazole ring. The FTIR (Fourier Transform Infra Red) characterization of lithium-5(6)-nitrobenzimidazole salts showed the disappearance of the peak at of 3300 - 3000 cm-1 which is peak vibration of –NH group. The synthesized lithium-5(6)-nitrobenzimidazole salt and poly(ethylene oxide) were used to form the polymer electrolyte membrane. The addition of 15% and 20% (w/w) of Li-5(6)-nitrobenzimidazole salt to poly(ethylene oxide) membrane could increase the Young Modulus value of the membrane from 0.9669 x 103 N m-2 to 1.405 x 103 N m-2 and 2.051 x 103 N m-2, respectively, with the conductivity value of 4.74 x10-7 S cm-1 and 4.89 x10-7 S cm-1, respectively.